Does the speaker matter? Online processing of semantic and pragmatic information in L2 speech comprehension. (August 2015) - Foucart, Alice; Garcia, Xavier; Ayguasanosa, Meritxell; Thierry, Guillaume; Martin, Clara; Costa, Albert
Abstract: The present study investigated how pragmatic information is integrated during L2 sentence comprehension. We put forward that the differences often observed between L1 and L2 sentence processing may reflect differences on how various types of information are used to process a sentence, and not necessarily differences between native and non-native linguistic systems. Based on the idea that when a cue is missing or distorted, one relies more on other cues available, we hypothesised that late bilinguals favour the cues that they master during sentence processing. To verify this hypothesis we investigated whether late bilinguals take the speaker's identity (inferred by the voice) into account when incrementally processing speech and whether this affects their online interpretation of the sentence. To do so, we adapted Van Berkum, J.J.A., Van den Brink, D., Tesink, C.M.J.Y., Kos, M., Hagoort, P., 2008. J. Cogn. Neurosci. 20(4), 580–591, study in which sentences with either semantic violations or pragmatic inconsistencies were presented. While both the native and the non-native groups showed a similar response to semantic violations (N400), their response to speakers' inconsistencies slightly diverged; late bilinguals showed a positivity much earlier than native speakers (LPP). These results suggest that, like native speakers, late bilinguals process semantic and pragmatic information incrementally; however, what seems to differ between L1 and L2 processing is the time-course of the different processes. We propose that this difference may originate from late bilinguals' sensitivity to pragmatic information and/or their ability to efficiently make use of the information provided by the sentence context to generate expectations in relation to pragmatic information during L2 sentence comprehension. In other words, late bilinguals may rely more on speaker identity than native speakers when they face semantic integration difficulties. Highlights: The time course of semantic and pragmatic processing is different in L2. Late bilinguals' sensitivity to pragmatic information is greater than natives'. Late bilinguals rely on indexical properties when semantic processing is complex.